How Influencer Content Credibility Drives Brand Co-creation: Do Social Presence and Consumers’ Psychological Well-being Matter? - Jerum William Kilumile; Li Zuo; Johakim Katekele John (SAGE Open)
With the advancement of social media, influencer content credibility can potentially drive consumer participation in brand co-creation. However, the impact of influencer content credibility on brand co-creation is underexplored, particularly the mechanism and process by which influencer content credibility impacts brand co-creation. Thus, this study employs social exchange theory and social presence theory to investigate how influencer content credibility affects brand co-creation, considering the mediating effect of consumers’ psychological well-being and the moderating effect of social presence. The study employed a 2 (influencer content credibility: high vs. low) × 2 (social presence: high vs. low) between-subjects experimental design, which enabled the establishment of cause-effect relationships by involving 213 respondents. Data were analyzed using an independent samples T-test, PLS -SEM, and a two-way ANOVA. The findings reveal that high influencer content credibility has a significant impact on brand co-creation. Besides, consumers’ psychological well-being partially mediates the effect of influencer content credibility on brand co-creation. Moreover, social presence moderates the impact of influencer content credibility on brand co-creation, such that the likelihood of consumers’ willingness to co-create brands is higher when high influencer content credibility is aligned with low social presence. Therefore, the theoretical integration in this study contributes to understanding influencer content credibility’s mechanism and conditional impacts on brand co-creation by highlighting the mediating role of psychological well-being and the moderating role of social presence in this process. The study offers practical insights for marketers on how to utilize influencer credible content and social presence to enhance brand co-creation while improving consumers’ psychological well-being.